Ocean Model Formulation Influences Transient Climate Response - Semmler, Tido; Jungclaus, Johann; Danek, Christopher; Goessling, Helge F.; Koldunov, Nikolay V.; Rackow, Thomas; Sidorenko, Dmitry; Jungclaus, Johann; 2 Max Planck Institute for Meteorology Hamburg Germany; Danek, Christopher; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Goessling, Helge F.; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Koldunov, Nikolay V.; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Rackow, Thomas; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; et al. (Journal of Geophysical Research: Oceans, 2021)
The transient climate response (TCR) is 20% higher in the Alfred Wegener Institute Climate Model (AWI‐CM) compared to the Max Planck Institute Earth System Model (MPI‐ESM) whereas the equilibrium climate sensitivity (ECS) is by up to 10% higher in AWI‐CM. These results are largely independent of the two considered model resolutions for each model. The two coupled CMIP6 models share the same atmosphere‐land component ECHAM6.3 developed at the Max Planck Institute for Meteorology (MPI‐M). However, ECHAM6.3 is coupled to two different ocean models, namely the MPIOM sea ice‐ocean model developed at MPI‐M and the FESOM sea ice‐ocean model developed at the Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI). A reason for the different TCR is related to ocean heat uptake in response to greenhouse gas forcing. Specifically, AWI‐CM simulations show stronger surface heating than MPI‐ESM simulations while the latter accumulate more heat in the deeper ocean. The vertically integrated ocean heat content is increasing slower in AWI‐CM model configurations compared to MPI‐ESM model configurations in the high latitudes. Weaker vertical mixing in AWI‐CM model configurations compared to MPI‐ESM model configurations seems to be key for these differences. The strongest difference in vertical ocean mixing occurs inside the Weddell and Ross Gyres and the northern North Atlantic. Over the North Atlantic, these differences materialize in a lack of a warming hole in AWI‐CM model configurations and the presence of a warming hole in MPI‐ESM model configurations. All these differences occur largely independent of the considered model resolutions. Plain Language Summary: The transient climate response (TCR) describes how strongly near‐surface temperatures warm in response to gradually increasing greenhouse‐gas levels. Here we investigate the role of the ocean which takes up heat and thereby delays the surface warming. Two models of the Coupled Model Intercomparison Project Phase 6 (CMIP6), the Alfred Wegener ...